Forensic Assistance Project: Consultant Report 1999-054 Foča I Federation Commission on Missing Persons - Bosniak Side - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Komar, Debra From September 13 through November 10, 1999, the Federation Commission on Missing Persons - Bosniak Side investigated a total of 57 sites near the town of Foča and exhumed a minimum of 83 individuals. The bodies were recovered from burned houses, single, double and mass graves and collections of surface remains. The Commission also repeatedly searched for a mass grave, suspected of containing in excess of two hundred people, but was unsuccessful. Place of Exhumation: Foča Exhumation Site: Miljevina, Mrđenovići I, Mrđenovići II, Miljevina II, Budanj, Budanj II, Budanj cemetery, Mjetvine, Mjetvine II, Ocrkavlje, Duškovici, Kljunc, Izbišno, Gradac, Lubure, Kratine, Kratine II, Trnjine, Crneta, Ratine, Ratine II, Ratine III, Ratine IV, Tekijska, TekijskaII, Ratine V, Radomišlje, Radomišlje II, Palež, Ratine VI, Sinice, Glavica, Selo Gouza, Jeleč, Ratine VII, Laza, Laza II, Podgaji, Podgaji II, Lepovičina, Unknown, Jeleč II, Poljice, Poljice II, Grabovik, Banjine, Poljice III, Čapljine, Poljice IV, Banjine II, Banjine III, Banjine lV, Banjine V, Močila, Ovšine, Glasjenica Date of Exhumation: 13 September - 10 November 1999 Minimum Number of Exhumed Individuals: 083